The comparison of erector spinae plane block and caudal block for postoperative analgesia in paediatric surgery - meta-analysis - Mahendratama Purnama Adhi; Rapto Hardian; Arif Budiman Susatya; Elizeus Elizeus; Arie Utariani (Medicinski glasnik, 2024)
Aim: To assess the efficacy of Erector Spinae Plane Block (ESPB) compared to caudal block in reducing postoperative pain in paediatric surgery. Methods: An electronic literature search was conducted using the Cochrane Library, PubMed, and Google Scholar databases, with data collected from January 2018 until September 2023. This meta-analysis includes English-language randomized controlled trials (RCTs) studies contrasting ESPB with caudal block in paediatric patients. The primary outcome was the 24-hour postoperative pain scores. The secondary outcome included the time to rescue analgesia, the number of patients requiring rescue analgesia, and the occurrence of postoperative nausea and vomiting (PONV) and urinary retention. Results: Five RCTs with 295 samples were included. The results showed no significant difference between ESPB and caudal block in postoperative pain scores at 1st hour SMD (standardized mean difference) of -0.17 (95% CI -0.70, 0.36; I2=76%; p= 0.53), 2nd hour of SMD: -0.50 (95% CI -1.21, 0.21; I2=88%; p=0.17), 6th hour SMD -1.09 (95% CI -2.21, 0.03; I2=95%; p = 0.06), 12th hour SMD -0.77 (95% CI -1.75, 0.21; I2=93%; p=0.12), and the 24th hour SMD -0.13 (95% CI -0.39, 0.12;, I2=2%; p=0.30) were found. Furthermore, there was no significant difference in the time first to rescue analgesia, the number of patients requiring analgesia rescue, PONV occurrence, and urinary retention. Conclusion: ESPB and caudal block showed equivalent analgesia efficacy and safety in paediatric surgery.
Keywords: erector spinae plane block; PONV; uri-nary retention; post-operative pain